Theoretical outlines for a complex approach to architecture - Alves, F. (2018)
This paper focuses on the built environment studying disciplines and their established or yet to establish connections with complex thought. It asks if there’s a path for the integration of Architecture and Urbanism on Complexity Theory. Complexity Theory is a disciplinary paradigm that often takes interdisciplinary stances upon looking at phenomenon that transcend the classically defined frontiers of science. Most phenomenon that ask for such an approach are emergent, as they represent a change in a system that cannot be irreducibly explained by decomposing it into its constituting parts. This idea allowed for complex ways to understand cities. Here, we use it to go forward on the built environment analysis and reach the building scale. If emergent phenomena result from interacting simple parts, firstly, one can imagine such simple parts to be people and their surroundings’ physical elements; but on a second look, technical advances allow us to design buildings’ physical elements as interacting parts themselves. If there’s optimization to be done in the building system, it will most certainly occur through linking these two points – as it allows for us to conceive open work adaptive structures that react to the stimulus of human occupation.